Respuesta :
The solutions of [tex]\log_3x + \log_3(x^2 + 2) = 1 + 2\log_3x[/tex] can be calculated using the logarithm rule.
The solution of [tex]\log_3x + \log_3(x^2 + 2) = 1 + 2\log_3x[/tex] is [tex]x=2[/tex] and [tex]x=1[/tex].
Given:
The expression is,
[tex]\log_3x + \log_3(x^2 + 2) = 1 + 2\log_3x[/tex]
What is a logarithm?
The logarithm is the inverse function of exponentiation. In logarithm base must be raised to yield a given number for an exponent. The following rule will use solve the given problem.
- [tex]\log_aa=1[/tex]
- [tex]\log_a(mn)=\log_am+\log_bn[/tex]
- [tex]\log_ax^n=n\log_ax[/tex]
Apply the above rule to solve the given problem.
[tex]\log_3x(x^2+2)=\log_33+\log_3x^2\\ \log_3x(x^2+2)=\log_33x^2\\ x(x^2+2)=3x^2[/tex]
Now, solve the above algebraic expression,
[tex]x^2-3x+2=0\\ x^2-2x-x+2=0\\ x(x-2)-1(x-2)=0\\ (x-2)(x-1)=0[/tex]
Thus, the solution of [tex]\log_3x + \log_3(x^2 + 2) = 1 + 2\log_3x[/tex] is [tex]x=2[/tex] and [tex]x=1[/tex].
Learn more about the logarithm rule here:
brainly.com/question/7302008
Answer:
x = 1
x = 2
Step-by-step explanation: correct on edg2022